Structure-based design and SAR development of 5, 6-dihydroimidazolo[1, 5-f]pteridine derivatives as novel Polo-like kinase-1 inhibitors. Issue 5 (1st March 2017) - Kiryanov, Andre; Natala, Srinivasa; Jones, Benjamin; McBride, Christopher; Feher, Victoria; Lam, Betty; Liu, Yan; Honda, Kouhei; Uchiyama, Noriko; Kawamoto, Tomohiro; Hikichi, Yuichi; Zhang, Lilly; et al.
Graphical abstract: Abstract: Using structure-based drug design, we identified a novel series of 5, 6-dihydroimidazolo[1, 5- f ]pteridine PLK1 inhibitors. Rational improvements to compounds of this class resulted in single-digit nanomolar enzyme and cellular activity against PLK1, and oral bioavailability. Compound1 exhibits >7 fold induction of phosphorylated Histone H3 and is efficacious in an in vivo HT-29 tumor xenograft model.